KARAKTERISASI DAN PEMBENTUKAN LIGNOSELULOFOAM DENGAN TEKNIK PENYEMPROTAN DAN PERENDAMAN PADA PROSES BLENDING ANTARA POLIMER LIGNOSELULOSA DAN POLIMER ISOPRENA - , Charles Banon, Prof. Drs. AH. Bambang Setiaji, M.Sc., Ph.D., Dr.rer.nat ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Formation of lignocellulofoam by mixing lignocellulose from cocodust with polyisoprene from natural rubber and blends of polyisoprene-sulfur as adhesives has been conducted. Blending lignocellulose and polyisoprene was performed by spraying and immersion technique with various concentrations of polyisoprene 3.67 to 16.53% (v/v) and sulfur addition with variation of 0.1, 0.2 to 0.5 g, on the optimum concentration of polyisoprene. The study was began by getting the cocodust from coconut husk using counter machine, separator and sifting. Cocodust was dried and sieved with 10 mesh size. Total of 30 g of cocodust was mixed with 100 mL of polyisoprene, molded and dried in an oven from (70, 75 to 90) oC until dry. The mechanical properties (strength and elasticity) were characterized by bending testing using Torsee-Tokyo testing machine. Bending strength and elasticity properties stated in the Modulus of Rupture (MOR) and Modulus of Elasticity (MOE). The lignocellulofoam density was determined by pycnometer method. Distribution molecule of lignocellulofoam was observed with a Transmission Electron Microscopy (TEM). Thermal stability of lignocellulofoam observed with DTA-TGA. The effect of the solubility to solvent on the mechanical properties of lignocellulofoam was indicated by decreasing value of MOR and MOE. The results showed that blending lignocellulose and polyisoprene in the preparation lignocellulofoam using the immersion technique is better than spraying technique with optimum conditions at a polyisoprene concentration of 11.02%. The addition of sulfur into polyisoprene concentration of 11.02% caused a decrease in bending strength and elasticity of lignocellulofoam. The molecule distribution analysis (TEM) showed addition of sulfur to the polyisoprene causing lignocellulose molecule immiscible distributed. The TGA/DTA analysis proved that the Weight and Heat Flow Endo Down stability of lignocellulofoam until 200oC. Immersion of the composite lignocellulofoam to kerosene, alkaline and acids, decrease the quality of the composite (MOR and MOE) of 53,5%